2020
DOI: 10.1111/jfpp.14827
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the microbiological quality of Argentinian Port Salut cheese by applying starch‐based films and coatings reinforced with rice bran and containing natural antimicrobials

Abstract: The demands of consumers for safer and better quality food have driven the development of new and less severe processing technologies, such as natural antimicrobials replacing synthetic chemicals and new packaging with active, intelligent, and edible systems (Ferndez Valdés et al., 2015). Focusing on the cheese, a very old product with different textures, flavor, and aromas, there are several critical points along cheese making, the storage stage is one of the most important stage. During this stage, the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Likewise, the integration of nisin in the chitosan-based films showed quite effective antimicrobial activity against different genera of species, suggesting its potent role in preservation systems applicable to various food products [1]. Thus, on a similar platform, research undertaken by Pintado et al [25], Ollé Resa et al [26], and Berti et al [27] reported the antimicrobial action of prepared films with both nisin and natamycin added.…”
Section: Antimicrobial Activity Of Treated Filmsmentioning
confidence: 87%
“…Likewise, the integration of nisin in the chitosan-based films showed quite effective antimicrobial activity against different genera of species, suggesting its potent role in preservation systems applicable to various food products [1]. Thus, on a similar platform, research undertaken by Pintado et al [25], Ollé Resa et al [26], and Berti et al [27] reported the antimicrobial action of prepared films with both nisin and natamycin added.…”
Section: Antimicrobial Activity Of Treated Filmsmentioning
confidence: 87%
“…Some researchers have developed edible coatings based on blends of starch with other natural polymers and/or food-grade additives for application on cheeses [9,10]. Berti et al, 2020 reported that the use of starch coatings reinforced with rice bran and containing nisin and natamycin was a useful strategy to prevent the post-process and external contamination of Argentinian Port Salut cheese [11].…”
Section: Introductionmentioning
confidence: 99%